2022
DOI: 10.3390/ijms23084226
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Ocular Diseases: A Systematic Review

Abstract: The contributory roles of vitamin D in ocular and visual health have long been discussed, with numerous studies pointing to the adverse effects of vitamin D deficiency. In this paper, we provide a systematic review of recent findings on the association between vitamin D and different ocular diseases, including myopia, age-related macular degeneration (AMD), glaucoma, diabetic retinopathy (DR), dry eye syndrome (DES), thyroid eye disease (TED), uveitis, retinoblastoma (RB), cataract, and others, from epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 310 publications
1
33
0
1
Order By: Relevance
“…However, Guggenheim et al were denied and found that serum vitamin levels were not substantially associated with the onset of myopia ( 8 ). Chan et al ( 21 ) conducted a systematic review, and the final results of their meta-analysis supported this position. A recent Mendelian randomization study demonstrated no association between DHCR7, CYP2R1, GC, and CYP24A1 gene-determined 25(OH)D levels and myopia severity ( 22 ).…”
Section: Discussionmentioning
confidence: 87%
“…However, Guggenheim et al were denied and found that serum vitamin levels were not substantially associated with the onset of myopia ( 8 ). Chan et al ( 21 ) conducted a systematic review, and the final results of their meta-analysis supported this position. A recent Mendelian randomization study demonstrated no association between DHCR7, CYP2R1, GC, and CYP24A1 gene-determined 25(OH)D levels and myopia severity ( 22 ).…”
Section: Discussionmentioning
confidence: 87%
“…There is growing evidence showing that vitamin D is endogenously produced by ocular tissues. 37 39 VDR expression is evident in the epithelium of the cornea, 40 lens, ciliary body, and retinal pigment epithelium as well as the corneal endothelium, retinal ganglion cell layer, and photoreceptors. 40 , 41 Given that VDR and vitamin D hydroxylases (CYP24A1 and CYP27B1) are expressed throughout the eye, characterizing their roles is a relevant approach to uncovering mechanisms that control ocular function in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Міопія нерозривно пов'язана зі зростанням очей і, таким чином, можливо, піддається впливу зміни стилю харчування. Дані літератури показують, що рівень вітаміну D 3 у сироватці крові має зворотний зв'язок з міопією і може асоціюватися із запобіганням її розвитку та прогресуванню [22,23]. Також немаловажне значення має рівень інших мікроелементів та антиоксидантів.…”
Section: обмін досвідом / Exchange Of Experienceunclassified